Assessment of staging, prognosis and mortality of colorectal cancer by tumor markers: receptor erbB-2 and cadherins. - Jesus, Eliane C [UNESP]; Matos, Delcio [UNESP]; Artigiani, Ricardo [UNESP]; Waitzberg, Angela F L [UNESP]; Goldenberg, Alberto [UNESP]; Saad, Sarhan Sydney [UNESP] (FapUNIFESP (SciELO), 2005)
PURPOSE: To evaluate the prognostic significance and correlation with staging and degree of cell differentiation of the tumoral expression of the proteins c-erbB-2 and E-cadherin, in patients with colorectal adenocarcinoma. METHODS: The study included 117 patients with an average age of 63.1 years and an average follow-up duration of 28.1 months. The disease-free interval, survival, incidence of recurrence and specific mortality were evaluated. c-erbB-2 anti-oncoprotein antibodies (Dako) were utilized via the streptavidin-biotin technique. Samples were considered to be positive for c-erbB-2 if 10% or more of the tumor cell membranes were stained.The anti-E-cadherin antibodies (Dako), evaluated this protein and is considered positive, if 50% or more of the cell membranes were stained. Statistical analysis was performed using Pearson's chi-squared test, Fisher's exact test, Kaplan-Meier's estimator, the log-rank test and Wilcoxon's test (Breslow version), setting the level of statistical significance at 5% (p<0.05). RESULTS: 52 of 108 patients studied for c-erbB-2 were positive (48.1%), 47 of 93 patients studied for E-cadherin were negative (50.5%). These data do not express any correlation with TNM (tumor, node and metastasis) staging and the degree of cell differentiation or with the tumor recurrence rate. The disease-free interval among patients who were positive for c-erbB-2 and negative for E-cadherin was 68.0 months and did not differ from those with c-erbB-2 negative and E-cadherin positive (55.0 months--p = 0.5510). The average survival among patients positive for c-erbB-2 and negative for E-cadherin was 75 months without statistical significance difference with the other group (61 months--p = 0.5256). Specific mortality occurred in 20.0% of the cases and did not correlate with the expression of c-erbB-2 (p=0.446), E-cadherin (p=0.883). CONCLUSION: The tumoral expression of c-erbB-2 and E-cadherin did not demonstrate a correlation with the staging and degree of cell differentiation, and it did not present prognostic value regarding disease recurrence, disease-free interval, survival and specific mortality among patients with colorectal adenocarcinoma.